Audit quality, family business and corporate governance mechanisms: the case of Morocco. Issue 4 (6th November 2017) - Nnadi, Matthias; Efobi, Uchenna; Oledinma, Akunna
Abstract : Purpose: The purpose of this paper is to investigate the effect of various corporate governance mechanisms such as board structure, ownership structure and debt level on the demand for better external audit quality. Design/methodology/approach: Using a sample of 142 non-financial Moroccan companies, the authors examine the impact of the above corporate governance mechanisms on the audit quality of firms. The empirical model is tested with firms which include family businesses as well as listed and non-listed Moroccan companies. Findings: The authors find a positive association between the demand for audit quality and the proportion of independent directors. The authors find evidence that the debt level has no impact on the demand for a better external audit; however, that there exists a complementary effect between the control exercised by independent directors and the demand for external audit quality. For ownership structure, the authors find a significant negative relation between the presence of blockholders and institutional investors and the demand for differentiated external audit quality, confirming the substitution hypothesis. Originality/value: The paper has practical importance for corporate governance mechanism and audit quality in the developing economies of Africa. The study highlights that most family businesses have efficient corporate governance mechanism and therefore do not need to rely on the big audit firms for quality audit.